Web applications on Azure : developing for global ccale - Reagan, Rob (Apress, 2018)
Build .NET apps on Microsoft Azure services that can grow to Internet scale. Learn how you can make smart application architecture decisions and follow best practices so that your website can handle tens of thousands of concurrent users and deliver your content globally. Author Rob Reagan takes you through key Azure technologies targeted toward building web applications, and along the way shares his lessons learned in scaling out real-world web applications. After an overview of web application building blocks, the book dives into relational and NoSQL data storage options on Azure, including Azure Table Storage and Cosmos DB. You'll then discover how to make best use of Redis Cache, WebJobs, Messaging Queues, and more, alongside other tips, tricks, and troubleshooting advice for when things go wrong. The book concludes with a thorough exploration of best practices for deployment at scale. What You'll Learn: Develop scalable web applications on Azure with ASP.NET MVC Understand the pros and cons of using SQL Azure vs. NoSQL solutions (Azure Tables, Cosmos DB) Perform data migration, backup, and recovery in SQL Azure Use effective caching Troubleshoot your web applications Know best practices for deployment.